2022
DOI: 10.3389/fmicb.2022.936021
|View full text |Cite
|
Sign up to set email alerts
|

Dysbiosis and predicted function of dental and ruminal microbiome associated with bovine periodontitis

Abstract: Extensive cattle livestock is advancing in Amazonia and its low productivity, with consequent pressure to open new areas, is partly due to sanitary problems and, among them, the periodontal diseases, whose environmental triggers or modifying factors are unknown. In this study, we used high-throughput sequencing, network analysis and predicted functions to investigate the dental and ruminal microbiota of cattle raised in new livestock areas in the Amazon and identify possible keystone pathogens and proteins ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…In the present study, the Gram-negative genera Bacteroides, Fusobacterium and Porphyromonas were the most abundant in the microbiota of deer abscesses. These genera have also been identified in great abundance in the oral microbiota of kangaroos with progressive periodontal disease (Yip et al 2021) and in domestic ruminants such as cattle, sheep and goats with periodontitis (Borsanelli et al 2018(Borsanelli et al , 2021(Borsanelli et al , 2022b(Borsanelli et al , 2022c. Some members of Fusobacterium genus can connect with different microorganisms, acting as a bridge between early colonizers and the latter periodontopathogens, including anaerobic Gram-negative like Bacteroides and Porphyromonas (Li et al 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the present study, the Gram-negative genera Bacteroides, Fusobacterium and Porphyromonas were the most abundant in the microbiota of deer abscesses. These genera have also been identified in great abundance in the oral microbiota of kangaroos with progressive periodontal disease (Yip et al 2021) and in domestic ruminants such as cattle, sheep and goats with periodontitis (Borsanelli et al 2018(Borsanelli et al , 2021(Borsanelli et al , 2022b(Borsanelli et al , 2022c. Some members of Fusobacterium genus can connect with different microorganisms, acting as a bridge between early colonizers and the latter periodontopathogens, including anaerobic Gram-negative like Bacteroides and Porphyromonas (Li et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Black-pigmented anaerobes belonging to Porphyromonas genus represent the most prevalent microorganisms in the microbiota of cattle, sheep, and goats with periodontitis and are associated with the disease in these animals (Borsanelli et al 2021(Borsanelli et al , 2022b(Borsanelli et al , 2022c. These microorganisms can express potent virulence factors and interfere with the host's innate immune response (Haffajee & Socransky 1994).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first isolation and characterization of F. flocculi occurred from sampling methanogenic granular sludge, and revealed that coculturing with hydrogenotrophic methanogens enhanced its growth [61]. In the dental and rumen microbiomes of cattle with periodontitis [62], network analyses have pointed to Flexilinea as being highly connected to other bacteria in the network. The authors hypothesized that cattle with periodontitis may produce more methane than healthy animals.…”
Section: Potential Bacterial Drivers Of Microbiome Dysbiosis In Cats ...mentioning
confidence: 99%
“…The rumen in healthy animals is dominated by Bacteroidetes (Christensenellaceae and Prevotellaceae) and Firmicutes (Erysipelotrichaceae). In diseased animals, Bacteroidetes (Prevotella and the Ricknellaceae) and Firmicutes (Erysipelotrichaceae) predominate [66].…”
Section: Disease Vectors-changes In the Microbiome In Pd Bm And CImentioning
confidence: 99%